Nucleotide sequence analysis of mitochondrial DNA hypervariable region II and inter HVR in Thais - Padchanee Sangthong (2020)
© 2019, © 2019 Australian Academy of Forensic Sciences. In this study, the nucleotide sequences of the mitochondrial DNA hypervariable region II (HVRII) and inter HVR in the Thai population were investigated. Buccal swab samples were randomly collected from 100 unrelated healthy individuals residing in Thailand. The analysis of HVRII revealed a total of 65 different haplotypes of which 47 were unique and 18 were found in more than one individual. The most frequent haplotype observed was A73G-A249D-A263G-309.1C–315.1C (7%). Nucleotide transition from adenine (A) to guanine (G) was the most frequent substitution. Nucleotide transversions were also observed but with a lower frequency compared to nucleotide transitions. Insertions of C (57%), CC (14%), and CCC (1%) were found at position 309. Twenty-six samples were found to exhibit nucleotide deletion at position 249. The haplotype diversity, random match probability, and discrimination power were calculated to be 0.9859, 0.0240, and 0.976 respectively. In addition, the outside HVR fragment within the control region at positions 16381–72 (inter HVRI/HVRII) and 341–437 (inter HVRII/HVRIII) were sequenced in order to examine the polymorphic sites. High polymorphism was found at positions 16519, 150, 249, and 309. It was concluded that the nucleotide sequence variations in HVRII and inter HVRI/HVRII would be useful for forensic identification.